Dilaoẏāra - Kazal, Ishaque (Ityādi Grantha Prakāśa, 2017)
Contributed articles on the life and works of Dilaoẏāra, born 1937, Bengali poet from Bangladesh
Keywords: Aufsatzsammlung; Dilaoẏāra 1937-; Poets; Bengali